Fatty Acid Composition of Assam Tea Seed Kernel Oils of Thailand - เทพกรณ์ ธีรพงษ์; พลอยศรี กาญจนา; เอกพันธ์ อนัญญา (KKU Science Journal, 2012)
The present research aims to determine the fatty acid profiles in seed kernel of Assam tea (Camellia sinensis var. assamica) of Thailand. Assam tea fruits were collected from Chiang Rai, Chiang Mai and Nan provinces. The tea seed kernels were separated and extracted by soxhlet extraction. The oil content of tea seed kernel was 12.22.1.32% w/w. The fatty acid profiles of tea seed kernel oils examined by GC/MS indicated that oil consisted of 55% oleic acid (C18:1), 21% linoleic acid (C18:2), 18% palmitic acid (C16:0), 4% stearic acid (C18:0) and 2% other fatty acids. The fatty acid profiles were compared with that of commercially tea oils (Camellia oleifera) and previous studies indicating that fatty acid profiles were similar to that of tea oils from Camellia sinensis.